2017
DOI: 10.1002/ajmg.a.38175
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and endocrine abnormalities in 22q11.2 deletion syndrome

Abstract: 22q11.2 deletion syndrome (22q11.2DS) has a wide range of clinical features including endocrine abnormalities. We aimed to characterize growth patterns, hypoparathyroidism, and thyroid dysfunction of individuals with 22q11.2DS. Anthropometric and laboratory measurements were obtained from the charts of 48 individuals (males=28, 8.0±6.8 visits/participant) followed at a national 22q11.2DS clinic between 2009 and 2016. Age at diagnosis was 4.3±4.9 years and age at last evaluation 11.2±7.2 years. Median height-SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…ATD is common among individuals with 22q11.2DS. Thyroid autoantibodies were found in up to 5% of affected children and 30% of patients older than 17 years (127,129,133,134) (Table 1). In the study of Shugar et al, overt thyroid disease was noted in 9.5% of 169 children with the syndrome.…”
Section: Q112 Deletion Syndromementioning
confidence: 99%
“…ATD is common among individuals with 22q11.2DS. Thyroid autoantibodies were found in up to 5% of affected children and 30% of patients older than 17 years (127,129,133,134) (Table 1). In the study of Shugar et al, overt thyroid disease was noted in 9.5% of 169 children with the syndrome.…”
Section: Q112 Deletion Syndromementioning
confidence: 99%
“…Furthermore, Tbx1 haploinsufficiency in mice produces embryos that exhibit facial dysmorphism typically associated with 22q11.2DS and that appeared smaller than the littermates [69]. In humans, a recent study of Israeli patients has indirectly supported the genetic effect on the ontogenetic disruption by finding no correlation between growth delays and palate anomalies or recurrent infections, and significant association with CHD [36].…”
Section: Discussionmentioning
confidence: 99%
“…infants and children) given velopharyngeal insufficiency and other gastrointestinal complications [4, 70]. In the second case, because, although it has been shown that there is a low prevalence of growth hormone deficiency in 22q11.2DS individuals, those patients with this endocrine disorder treated with growth hormone show growth improvement [36], even when an adequate dietary intake showed no results [71]. In the last case, given that CHD is commonly observed in patients and a recent study shows promising results that suggest that the embryonic treatment using vitamin B12 ameliorates Tbx1 gene haploinsufficiency in mice [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid disorders are caused by either autoimmune processes or congenital malformations of thyroid lobes ( 3 ). Growth failure correlates with congenital heart defects ( 7 ) or feeding problems ( 1 , 8 ), and the prevalence of growth hormone deficiency has been reported to be 4% ( 9 ). Previous studies have found that patients with 22q11.2DS experience retarded growth during childhood followed by a period of catch-up growth ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%